The Effects of Extraction Period Toward Anthocyanin Levels of Blue Pea Vine (Clitoria ternatea) Extract Using Maceration Method - Irna Dwi Destiana; Atika Romalasari; Nia Kurnia (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2021)
Blue Pea Vine (Clitoria Ternatea L.) is an edible flower which is rich in compounds of anthocyanin. The purpose of this research is to determine the best immersion time for anthocyanin extraction of blue pea vine by using maceration method. It also attempts to reveal the anthocyanin content, as well as the color and pH from blue pea vine extraction. Three treatments were treated with two replications, namely the first treatment of soaking is for 24 hours, 48 hours and 72 hours. The best soaking time in the treatment was 48 hours which resulted the highest anthocyanin content of 172,833 mg/100g. The color result was based on the level of attention to the achromatic color from the extraction of 48 hours of blue connection with an L* value of 25.95, the a* value of -0.4, and b* value of 1.35. The pH value result is pH 4.61